Cyclophosphamide for Refractory Acute Cellular Rejection After Lung Transplantation. Issue 5 (May 2018) - Naik, Chetan; Moore, Cody; Pipeling, Matthew; D'Cunha, Jonathan; Ruppert, Kristine; Ensor, Christopher; Morrell, Matthew
Abstract : Background: Acute cellular rejection (ACR) is a major risk factor for chronic lung allograft dysfunction after lung transplantation. Acute cellular rejection can persist or recur despite augmentation of immunosuppression by conventional methods. There are limited therapeutic options in treating these recurrent and refractory ACRs. We describe our experience with cyclophosphamide therapy for recurrent and refractory ACR in lung transplant recipients. Methods: Six consecutive patients who were treated with cyclophosphamide for recurrent or refractory ACR were included in the series. The primary outcome measures were improvement in ACR score and forced expiratory volume at 1 second. Secondary outcome measures included adverse drug events including bone marrow suppression, gastrointestinal side effects, and infections. Results: Five of the 6 patients treated demonstrated complete resolution of ACR on follow-up biopsies. Acute cellular rejection score improved after cyclophosphamide treatment ( P = 0.03). None of the patients had high grade (≥A3) ACR in the 3 months after cyclophosphamide administration. Cyclophosphamide had no effect on forced expiratory volume at 1 second trend or bronchiolitis obliterans score. All patients tolerated cyclophosphamide with minor gastrointestinal side effects, mild bone marrow suppression, and nonfatal infections that were amenable to treatment. Conclusions: Cyclophosphamide therapy is an option in treating recurrent and refractory ACR in patients who have failed conventional treatments. Cyclophosphamide is tolerated well without serious adverse drug events (ADE).